A VIOLÊNCIA CONTRA AS MULHERES NA VIDA COTIDIANA Um estudo do Livro da Aliança a partir de Êxodo 20,22-23,19 - Brancher, Mercedes (2004)
The social space beneath the literary unity of Exodus 20: 22-23, 19 presupposes an agrarian society, apparently monoto us, but marked by innumerable social conflicts. The social context is one of the poverty of the Israelite clan - tribes families. The new economy is organized around the sanctuary. There is considerable research consensus as to the origin of the literary unit know as the Book of the Covenant. It represents juridical literature of a religious character. A juridical prescription does not precede the conditions of reality to which it refers, but prescribes regarding the conditions and situations that already exist. Two general currents exist in classic research regarding the origin and epoch of this literature. One defends the thesis that the Book of the Covenant belongs to the pre-state period, and the transition from tribalism to monarchy; the other argues that the Book of the Covenant, as a codification of laws in a single corpus, is the product of a later period, possibly appearing at the end of the VIII century, or the beginning of the VII before Christ. The Book of the Covenant is the literary base of the present research. As to the origin and epoch of the Book of the Covenant, this research follow the current of thought that defends the text as coming from the final epoch of the tribal earlier period of the monarchy. This epoch was marked by great economic changes, specifically the passage from an isolated subsistence economy to an economy that concentrated on production. The thesis consists of an analysis of violence against women, structured in the juridical discourse of the Book of the Covenant. The thesis seeks to reveal the mechanisms that justify and treat violent practices as natural. Violence against women slaves, daughters and, especially, women considered to be sorcerers are given special attention. Three categories of female slaves present in the text are considered: domestic slaves, that suffer physical violence that potentially result in death by whipping; temporary slaves, that have their eyes destroyed and teeth broken; and daughters that are sold as slaves. Their sexuality is transformed into a commodity. There are also daughters that are seduced, violated and submitted to treatment as one of the woman of their rapist. Women considered as sorcerers are the only social group described according to their public function. The violence described is institutional and sexist. Patriarchy is the organizing principle of society. The characteristic of the Book of the Covenant is markedly androcentric.(AU)